Preference of Skincare Product Usage Among Students of Public Health Faculty of Nusa Cendana University - Badur, Anjelina Kurniati; Adu, Apris A; Wijaya, R. Pasifikus Ch; Junias, Marylin Susanti (Universitas Nusa Cendana, 2024)
Skincare product preference is an individual's interest in seeing and choosing certain skincare products that are the primary, most desirable, and are a priority choice. This study aims to determine the description of skincare product preferences and the impact of product use psychologically on students of the Faculty of Public Health, Nusa Cendana University Kupang. The type of research used is the mixed method. The research participants used the purposive sampling technique of 300 students of the Faculty of Public Health, Nusa Cendana University Kupang. The descriptive analysis results show that skincare products with the highest number of preferences are face wash (73.3%). The thematic analysis results indicate that students choose skincare products that can protect the skin, help solve skin problems, and brighten the skin. Psychologically, the use of skincare products makes students feel more confident.